Sexual Harassment in Boys: An Overview of Child Victims and Child Perpetrators in Indonesia - Urbayatun, Siti; Asmorojati, Anom Wahyu; Agusta, Rendra (SCAD Independent, 2023)
There are still few studies on sexual harassment toward boys. In society, there is still a lot of skepticism and stigma about whether boys can be perpetrators or victims of sexual harassment. The purpose of this study was to explore the occurrence of sexual violence towards boys, such as the dynamics of the perpetrators and victims, the motivation of the perpetrators to commit sexual violence, and the impact of sexual violence on victims. This study used a descriptive qualitative method, with 17 subjects aged 0–18. The data collection used a study of documents collected from trial facts in the Directory of Supreme Court Decisions. The data were analyzed by the N-Vivo application for data processing, management, ideas, queries, visualization, and reporting. This study found that imitation was the main trigger for perpetrators to commit sexual harassment. From the victim's side, the impact the victim feels is a feeling of trauma, depression, and sensitivity. The role of the environment and online media needs attention in preventing and handling sexual violence against children.